Emotional intelligence of employees at PT Bumi Sarana Beton Makassar - Andi Tenry Sose; Darmawati Manda; Andi Idham Ashar (Universitas Negeri Makassar, 2022)
Emotional intelligence will give awareness, namely the consciousness of din or awareness, which is the most important emotional ability to train internal control. The purpose of this research is to know the emotional intelligence of employees at PT. Bumi Sarana Beton Makassar. This research uses quantitative descriptive research aimed at providing an overview of the level of Spiritual intelligence on the performance improvement of PT. Bumi Sarana Beton Makassar. The population of this research is all employees scope PT. Earth facilities Concrete, amounting to 35 people, the way the sampling is used is a saturated sample so all population members are used as samples. The results showed that emotional intelligence was not instrumental in the performance of employees. The structure of public organisations where decision-making from the top down makes emotional intelligence have no influence on employee performance.